2022
DOI: 10.3390/ma15051668
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Curing Regime on the Mechanical Strength, Hydration, and Microstructure of Ecological Ultrahigh-Performance Concrete (EUHPC)

Abstract: This paper investigates the effect of curing regimes (standard and steam curing) on the mechanical strength, hydration, and microstructure of ecological ultrahigh-performance concrete (EUHPC). The flowability, compressive strength, flexural strength, hydration, porosity, pore size distribution, and microstructure of UHPC with different contents of supplementary materials (silica fume, fly ash, and ground granulated blast furnace slag) were assessed. The test results showed that the compressive strength of EUHP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Tanvir Ahmed found that compressive strength, flexure and tensile strength reduced 54%, 56% and 54% due to varying percentages of fly ash and w/b ratio of mixes [18]. Zhiwu Zuo found an increase in compressive and flexural strengths of UHPC at 28 days, 161.5 MPa and 44.9 MPa under steam curing, compared to standard room curing [19]. Šahmenko used short steel fiber (SSF), carbon fiber (CF), and combination for both high strength and fracture energy [20].…”
Section: Performance Of Uhpc and Sustainabilitymentioning
confidence: 99%
“…Tanvir Ahmed found that compressive strength, flexure and tensile strength reduced 54%, 56% and 54% due to varying percentages of fly ash and w/b ratio of mixes [18]. Zhiwu Zuo found an increase in compressive and flexural strengths of UHPC at 28 days, 161.5 MPa and 44.9 MPa under steam curing, compared to standard room curing [19]. Šahmenko used short steel fiber (SSF), carbon fiber (CF), and combination for both high strength and fracture energy [20].…”
Section: Performance Of Uhpc and Sustainabilitymentioning
confidence: 99%
“…Also ascertained that concrete attained higher strength and durability with Wet sand curing method than other curing methods (Immersing in water, Water spraying, apply curing compound and No curing) and immersing in water curing concrete properties closer to Wet sand curing concrete properties. Zuo et al [15] investigated the effect of curing regimes (standard and steam curing) on the mechanical strength, hydration, and microstructure of ecological ultrahigh-performance concrete (EUHPC). The test results showed that the compressive strength of EUHPC under steam curing was increased considerably compared to that under standard curing, while the flexural strength was mildly decreased.…”
Section: Introductionmentioning
confidence: 99%